2017
DOI: 10.1128/iai.00966-16
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of Clostridium botulinum C2 Toxin Requires Acid Sphingomyelinase Activity

Abstract: Clostridium botulinum C2 toxin consists of an enzyme component (C2I) and a binding component (C2II). Activated C2II (C2IIa) binds to a cell receptor, giving rise to lipid raft-dependent oligomerization, and it then assembles with C2I. The whole toxin complex is then endocytosed into the cytosol, resulting in the destruction of the actin cytoskeleton and cell rounding. Here, we showed that C2 toxin requires acid sphingomyelinase (ASMase) activity during internalization. In this study, inhibitors of ASMase and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…[29,30] Recently,the distribution of sphingolipids in the plasma membrane of cells has been investigated by super-resolution microscopy. [31,32] Furthermore,h igh-resolution imaging mass spectrometry has been used to map the distribution of 15 N-enriched ions from metabolically labeled 15 N-sphingolipids with about 50 nm lateral resolution and an analysis depth of < 5nmtoensure the selective investigation of membrane sphingolipids. [33] Thes tudy revealed the existence of micrometer-scale sphingolipid platforms with amean diameter of about 200 nm, independent of fixation conditions and temperature.…”
mentioning
confidence: 99%
“…[29,30] Recently,the distribution of sphingolipids in the plasma membrane of cells has been investigated by super-resolution microscopy. [31,32] Furthermore,h igh-resolution imaging mass spectrometry has been used to map the distribution of 15 N-enriched ions from metabolically labeled 15 N-sphingolipids with about 50 nm lateral resolution and an analysis depth of < 5nmtoensure the selective investigation of membrane sphingolipids. [33] Thes tudy revealed the existence of micrometer-scale sphingolipid platforms with amean diameter of about 200 nm, independent of fixation conditions and temperature.…”
mentioning
confidence: 99%
“…Recently, we demonstrated that C2 toxin needs the activity of acid sphingomyelinase (ASMase) during the initial step of endocytosis [ 41 ]. Several bacterial pore-forming cytotoxic proteins cause calcium entry and provoke the exocytosis of lysosomes, leading to the release of lysosomal ASMase to the extracellular medium [ 42 , 43 ].…”
Section: C Botulinum C2 Toxinmentioning
confidence: 99%
“…Namely, the hydrolysis of sphingomyelin by ASMase secreted from the exocytosis of lysosomes produces plasma membrane microdomains enriched in ceramide, leading to endocytosis [ 44 , 45 ]. C2IIa causes the entry of extracellular calcium into sensitive cells, and the cytotoxic activity of C2 toxin is increased in calcium-containing medium [ 41 ]. Blockers of lysosomal exocytosis and ASMase inhibit the cytotoxic activity of C2 toxin.…”
Section: C Botulinum C2 Toxinmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Moreover, SMases and ceramides have been shown to be critically involved in the internalization of pathogens. [10][11][12][13][14][15] The recent observation, that CRP formation is essential in controlling the metabolic activity of regulatory T cells demonstrates that ceramides play also an essential role in regulating immune functions and inflammation. [16,17] However, despite these important roles the molecular organization of ceramides in the plasma membrane remains elusive.…”
mentioning
confidence: 99%